Generalized Anxiety Disorder and Hypoglycemia Symptoms Improved with Diet Modification - Monique Aucoin; Sukriti Bhardwaj (Case Reports in Psychiatry)
Observational evidence suggests that a relationship may exist between high glycemic index diets and the development of anxiety and depression symptoms; however, as no interventional studies assessing this relationship in a psychiatric population have been completed, the possibility of a causal link is unclear. AB is a 15-year-old female who presented with concerns of generalized anxiety disorder and hypoglycemia symptoms. Her diet consisted primarily of refined carbohydrates. The addition of protein, fat, and fiber to her diet resulted in a substantial decrease in anxiety symptoms as well as a decrease in the frequency and severity of hypoglycemia symptoms. A brief return to her previous diet caused a return of her anxiety symptoms, followed by improvement when she restarted the prescribed diet. This case strengthens the hypothesis that dietary glycemic index may play a role in the pathogenesis or progression of mental illnesses such as generalized anxiety disorder and subsequently that dietary modification as a therapeutic intervention in the treatment of mental illness warrants further study.